2021
DOI: 10.1111/1440-1630.12772
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 restrictions on occupational balance: A mixed method study of the experience of Australian occupational therapists

Abstract: Introduction COVID‐19 has seen unprecedented changes to the daily occupational lives of citizens across the globe as a result social and physical restrictions. Frontline healthcare workers health and wellbeing have been impacted but what of occupational balance? The aim of this study was to investigate if there was a change in the occupational balance of occupational therapists working in a metropolitan hospital during a COVID‐19 lockdown. Methods All occupational therapists working in a metropolitan hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Hence, the stressors and buffers identified here were not mutually exclusive and sometimes posed contradictions within our socioecological framework in a similar manner to previous work that identified both negative and positive critical events among physical therapists (Palacios-Ceña et al , 2021 a). Our findings therefore resonate with past work employing quantitative (Hoel et al , 2021 ; Yang et al , 2020 ), qualitative (Palacios-Ceña et al , 2021 a; Palacios- Ceña et al , 2021b), and mixed-methods (Tse et al , 2021 ) approaches by expanding on and bridging their respective findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Hence, the stressors and buffers identified here were not mutually exclusive and sometimes posed contradictions within our socioecological framework in a similar manner to previous work that identified both negative and positive critical events among physical therapists (Palacios-Ceña et al , 2021 a). Our findings therefore resonate with past work employing quantitative (Hoel et al , 2021 ; Yang et al , 2020 ), qualitative (Palacios-Ceña et al , 2021 a; Palacios- Ceña et al , 2021b), and mixed-methods (Tse et al , 2021 ) approaches by expanding on and bridging their respective findings.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies reported elevated anxiety, depression, and reduced morale across therapist participants (Hoel et al , 2021 ; Yang et al , 2020 ) . Others reported minimal adverse effects (Tse et al 2021 ) or the occurrence of positive feelings related to personal and professional growth embedded in an “emotional roller coaster” (Palacios-Ceña et al , 2021 a). This study contributes a unique angle to this discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can justify the increase in an occupational imbalance during one to three months after hospitalization in the present study, while occupational balance did not decrease in healthy individuals. Therefore, the activity patterns and the balance between them were related to individuals' mental and physical health (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the energy-saving technique, which means prioritizing tasks during the day, is a method to control fatigue. Furthermore, improving mental health and maintaining the occupational balance after hospitalization due to COVID-19 can be achieved through increasing social support (39) and emotional support from the family, daily planning, performing valuable personal and social activities, high work activity levels, exercise, and doing regular physical activities (34). Various studies indicate that people who had problems due to their daily activity patterns, could regain their occupational balance only by making changes in daily activity patterns, the way of performing activities, and prioritizing them.…”
Section: Discussionmentioning
confidence: 99%